A new holistic systems approach to the design of heat treated alloy steels using a biologically inspired multi-objective optimisation algorithm. (January 2015) - Chen, Jun; Mahfouf, Mahdi; Sidahmed, Gaffour
Abstract: The primary objective of this paper is to introduce a new holistic approach to the design of alloy steels based on a biologically inspired multi-objective immune optimisation algorithm. To this aim, a modified population adaptive based immune algorithm (PAIA2) and a multi-stage optimisation procedure are introduced, which facilitate a systematic and integrated fuzzy knowledge extraction process. The extracted (interpretable) fuzzy models are able to fully describe the mechanical properties of the investigated alloy steels. With such knowledge in hand, locating the 'best' processing parameters and the corresponding chemical compositions to achieve certain pre-defined mechanical properties of steels is possible. The research has also enabled to unravel the power of multi-objective optimisation (MOP) for automating and simplifying the design of the heat treated alloy steels and hence to achieve 'right-first-time' production. Highlights: We model mechanical properties of heat treated alloy steel using interpretable fuzzy models. We demonstrate how to locate the 'best' processing parameters and chemical compositions. We demonstrate how to achieve certain mechanical properties. We demonstrated a holistic systems approach to achieve 'right-first-time' production. We unravel the power of multi-objective optimisation and interpretable fuzzy modelling.